2012
DOI: 10.3748/wjg.v18.i10.1059
|View full text |Cite
|
Sign up to set email alerts
|

Rebamipide suppresses diclofenac-induced intestinal permeabilityviamitochondrial protection in mice

Abstract: Increased intestinal permeability induced by diclofenac can be attenuated by rebamipide, which partially contributed to the protection of mitochondrial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 34 publications
1
8
1
2
Order By: Relevance
“…FITC-D and Evans blue are non-absorbed macromolecules that are used as indicators of intestinal permeability [22]. In our study, we found that treatment with ghrelin significantly attenuated FITC-D and Evans blue leakage following ICH, thus reducing the intestinal permeability.…”
Section: Discussionsupporting
confidence: 52%
“…FITC-D and Evans blue are non-absorbed macromolecules that are used as indicators of intestinal permeability [22]. In our study, we found that treatment with ghrelin significantly attenuated FITC-D and Evans blue leakage following ICH, thus reducing the intestinal permeability.…”
Section: Discussionsupporting
confidence: 52%
“…Rat liver mitochondria were used for these studies, because purified healthy mitochondria from intestinal tissues could not be obtained in sufficient yields. However, it is accepted that there are no significant differences between mitochondria isolated from different organs in their response to uncoupling agents or inhibitors of the respiratory chain (Tyler, 1991;Diao et al, 2012). The liver mitochondrial suspension was then divided into two aliquots: one (2 mg/ml mitochondrial proteins) was used to evaluate the mitochondrial membrane potential, and the other one (0.8 mg/ml mitochondrial proteins) was used to characterize mitochondrial respiration by recording oxygen consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Cinaciguat did not influence jejunal strips, either when contracted by PGF 2 α or by carbachol; two different contractile agents were used to exclude the possibility that the non‐effect of cinaciguat is related to the contractile agent used, as it was reported before that different contractile agents can affect the ability to induce smooth muscle relaxation . Cinaciguat is expected to be more efficient when sGC is in the heme‐oxidized condition, but MDA/HNE levels in antrum and jejunum were similar to those in colon and fundus; the MDA/HNE values were also comparable to those reported in the literature for mouse small intestine (0.97 nmol/(mg protein)), rat small intestine (2.09 nmol/(mg protein)), and rat colon (1.17 nmol/(mg protein)) . We have thus no explanation for the lack of effect of cinaciguat in WT and apo‐sGC antrum and jejunum, nor for its ineffectiveness in the pylorus of apo‐sGC mice.…”
Section: Discussionmentioning
confidence: 95%